The Role of Digital Tecnology in Improving HR Management Efficiency: A Case Study at Al Madina Foundation - Hidayat, Muhamad Hasim Fajar; Rizal, Achmad; Ulinuha, Arjun Albana; Azka, M. Gilang Maulana (UM Purwokerto Press, 2025)
The focus of this study is the identification of technologization of HR management processes and the ways to overcome the existing obstacles and its effect on the employees’ productivity and competency development. The research method used is qualitative by case study approach. The data were gathered through in depth interview, participatory observation and internal document review related to the implementation of digital technologies in the human resource management processes. The subjects of the study are managers, staff including educators of Yayasan Al Madina in relation to the digital transformation. Thematic content analysis was employed to analyze the data in order to find significant patterns from the collected data. This research provides benefits in the form of a deeper understanding of the relationship between digital technology and human resource management, and offers practical guidance for HR managers at Al Madina Foundation and similar institutions to optimize the use of digital technology in improving operational efficiency.